2018
DOI: 10.3390/en11040884
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy Saving Potential in High-Performance Building Technologies under Korean Climatic Conditions

Abstract: This study aims to suggest a basis for the selection of technologies for developing high-performance buildings to reduce energy consumption and greenhouse gas emissions. Energy-saving technologies comprising 15 cases were categorized into passive, active, and renewable energy systems. EnergyPlus v8.8.0 was used to analyze the contribution of each technology in reducing the primary energy consumptions and CO 2 emissions in the Korean climate. The primary energy consumptions of the base model were 464.1 and 485.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
(109 reference statements)
1
6
0
Order By: Relevance
“…Since there is no study that compares all four systems in various climates, we need to review the simulation data by applying it in different climates. However, data analyzed in this study showed similar results as those of Cho et al [69] and Kim et al [14] who studied various energy-saving systems in the Korean climate.…”
Section: Limitation Of Research and Future Worksupporting
confidence: 87%
See 1 more Smart Citation
“…Since there is no study that compares all four systems in various climates, we need to review the simulation data by applying it in different climates. However, data analyzed in this study showed similar results as those of Cho et al [69] and Kim et al [14] who studied various energy-saving systems in the Korean climate.…”
Section: Limitation Of Research and Future Worksupporting
confidence: 87%
“…An HVAC system is a component that unavoidably consumes energy with the purpose of providing a comfortable human living space. Energy-conserving HVAC systems continue to be studied and installed and can replace conventional HVAC systems to significantly reduce greenhouse gas (GHG) emissions [14,15]. To effectively reduce the energy used in an air-conditioning system, we should understand the characteristics of each system, and analyze each element that consumes energy.…”
Section: Background and Purposementioning
confidence: 99%
“…Accurate estimation of indoor daylight illuminance is important in saving lighting energy, as indoor daylight illuminance data can be used to predict a building's lighting energy and improve energy efficiency. Especially in a general office building, lighting energy consumption is responsible for 20%-30% of the total building energy consumption [3][4][5][6], and the effective control of daylight can reduce lighting energy consumption by 30%-60% annually [7][8][9].…”
Section: Background and Purposementioning
confidence: 99%
“…South Korea is mainly divided into three climate zones: central, southern, and Jeju. According to Köppen classification, the central climate zone is classified as Dwa characterized by cold-dry winter and hot summer while the southern and Jeju climate zones are classified as Cfa (temperate region, humid year-round, and hot summer) [16]. Given that the central and southern zones make the biggest part of the country, the two cities used in this study, Seoul and Ulsan, were selected from the central and southern climate zones, respectively, as is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%